Multimodal investigations of structural and functional brain alterations in anorexia and bulimia nervosa and their relationships to psychopathology: archival report - Yu, Xinyang; Robinson, Lauren; Bobou, Marina; Zhang, Zuo; Banaschewski, Tobias; Barker, Gareth J.; Bokde, Arun L. W.; Flor, Herta; Grigis, Antoine; Garavan, Hugh; Gowland, Penny; Heinz, Andreas; et al. (Biological psychiatry, 2025)
Background - Neurobiological understanding of eating disorders (EDs) is limited. This study presents the first comparative multimodal magnetic resonance imaging assessments of anorexia nervosa and bulimia nervosa and uncovers neurobiological differences associated with these disorders. - Methods - This case-control study included 57 healthy female control participants and 130 female participants with EDs (bulimia nervosa and anorexia nervosa subtypes). Structural and functional magnetic resonance imaging assessed gray matter volume (GMV), cortical thickness, and task-based activities related to reward processing, socioemotional functioning, and response inhibition. Whole-brain group differences were correlated with ED psychopathology. - Results - Significant structural differences were observed in the ED group compared with healthy control participants, including reduced GMV in the left lateral orbitofrontal cortex and lower cortical thickness in the left rostral middle frontal gyrus and precuneus after adjusting for body mass index. Specific structural alterations were only evident in anorexia nervosa subgroups. GMV reductions in the orbitofrontal cortex were linked to impulsivity, while lower cortical thickness in the frontal gyrus correlated with cognitive restraint in eating, suggesting that these regions may play key roles in ED psychopathology. Functional magnetic resonance imaging also revealed notable differences. During reward anticipation, participants with EDs exhibited deactivations in the cerebellum and right superior frontal gyrus together with reduced activation in the left lingual gyrus. These functional changes were associated with heightened neuroticism. Mediation analyses suggested that starvation-related GMV reductions in EDs disrupt reward-related brain function, increase neuroticism, and reinforce cognitive restraint, likely contributing to the persistence of ED symptoms. - Conclusions - These findings illuminate key neurobehavioral mechanisms that underlie EDs and point to potential brain-based targets for developing specialized treatment.
Online verfügbar: 23. November 2024, Artikelversion: 9. Juli 2025
Gesehen am 21.08.2025